Environmental Education and Education for Sustainability: history, fundamentals and/Educación Ambiental y Educaciòn para la Sostenibilidad: historia, fundamentos y tendencias. (Encuentros, 2019)
The proposed challenges in education in this century educator demand a proactive and self-training, which means that it must use different ways of approaching and understanding the environmental dynamics with which interacts from complexity. Coupled with this, the educator should understand the fundamentals and trends in the types of education that emerged between 1970-2014, including: environmental education (EE) and Education for Sustainable Development (ESD). In this context it is appropriate to ask: What will kind of education that branch or complement ?, what are the purposes of each ?, What theoretical and methodological aspects characterize what are the foundations and pedagogical trends are are that sustain? How they have developed in Venezuela? To answer these questions a documentary research was developed in order to analyze the historical journey of EE and ESD under international guidelines, its fundamentals and trends. The methodology used for the research was content analysis, establishing four categories: key concepts, implicit and explicit theories, paradigm and educational trends grouped in dimensions. The results were organized following the technical description and the conceptual system of Grounded Theory (Strauss & Corbin, 2002). Are obtained as a result the state of the art of EA and EDS in four decades, both described from the properties that characterize the dimensions: conceptual, institutional and pedagogicalKeywords: Environmental Education; Education for Sustainable Development; teaching basics of EA and EDS; trends EDS and EA; EA history and EDS.